Targeting the Akt, GSK-3, Bcl-2 axis in acute myeloid leukemia. (August 2017) - Ricciardi, Maria Rosaria; Mirabilii, Simone; Licchetta, Roberto; Piedimonte, Monica; Tafuri, Agostino
Abstract: Over the last few decades, there has been significant progress in the understanding of the pathogenetic mechanisms of the Acute Myeloid Leukemia (AML). However, despite important advances in elucidating molecular mechanisms, the treatment of AML has not improved significantly, remaining anchored at the standard chemotherapy regimen "3 + 7", with the prognosis of patients remaining severe, especially for the elderly and for those not eligible for transplant procedures. The biological and clinical heterogeneity of AML represents the major obstacle that hinders the improvement of prognosis and the identification of new effective therapeutic approaches. To date, abundant information has been collected on the genetic and molecular alterations of AML carrying prognostic significance. However, not enough is known on how AML progenitors regulate proliferation and survival by redundant and cross-talking signal transduction pathways (STP). Furthermore, it remains unclear how such complicated network affects prognosis and therapeutic treatment options, although many of these molecular determinants are potentially attractive for their druggable characteristics. In this review, some of the key STP frequently deregulated in AML, such as PI3k/Akt/mTOR pathway, GSK3 and components of Bcl-2 family of proteins, are summarized, highlighting in addition their interplay. Based on this information, we reviewed new targeted therapeutic approaches, focusing on the aberrant networks that sustain the AML blast proliferation, survival and drug resistance, aiming to improve disease treatment. Finally, we reported the approaches aimed at disrupting key signaling cross-talk overcoming resistances based on the combination of different targeting therapeutic strategies.